2017
DOI: 10.1097/rlu.0000000000001814
|View full text |Cite
|
Sign up to set email alerts
|

68Ga-DOTA-TATE PET/CT for Molecular Imaging of Somatostatin Receptor Expression in Metastasizing Epithelioid Hemangioendothelioma

Abstract: Epithelioid hemangioendothelioma (EHE) is a rare tumor originating from vascular endothelial or pre-endothelial cells. It has the potential to metastasize. We present the case of a 51-year-old woman with metastasizing EHE who underwent both F-FDG and Ga-DOTA-TATE PET/CT for staging of disease and for evaluation of targeted radionuclide therapy potential. On Ga-DOTA-TATE PET scans, intense tracer accumulation was observed in metastases. Besides the increased glucose metabolism in EHE, this case highlights the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Epithelioid hemangioendothelioma (EHE) is a rare low-grade tumor originating from vascular endothelial or pre-endothelial cells with the potential to metastasize and recur [ 89 ]. Derlin et al [ 74 ] described a case where [ 68 Ga]Ga-DOTATATE and [ 18 F]FDG identified vertebral metastasis from EHE. [ 68 Ga]Ga-DOTATATE demonstrated a higher tumor to background ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Epithelioid hemangioendothelioma (EHE) is a rare low-grade tumor originating from vascular endothelial or pre-endothelial cells with the potential to metastasize and recur [ 89 ]. Derlin et al [ 74 ] described a case where [ 68 Ga]Ga-DOTATATE and [ 18 F]FDG identified vertebral metastasis from EHE. [ 68 Ga]Ga-DOTATATE demonstrated a higher tumor to background ratio.…”
Section: Discussionmentioning
confidence: 99%
“…68 Ga-DOTA-NOC, consisting of 68 Ga-DOTA (1,4,7,10-Tetraazacyclododecane-1,4,7,10-tetraacetic acid) complex conjugated to the somatostatin analog 1 (1-NaI3-octreotide, NOC) has been used for the detection of a broad range of tumor types and their metastases, as for example parotid basal cell adenoma, medulloblastoma, neuroblastoma and bronchial carcinoids [47][48][49][50]. Another complex using a different somatostatin analog (Tyr3-octreotate, TATE), 68 Ga-DOTA-TATE has also been used in several tumor-type detection and is part of ongoing clinical trials for metastatic castration-resistant prostate cancer diagnostics [51,52]. Edotreotide (TOC), with a special affinity for type 2 somatostatin receptors has also been used combined with 68 Ga-DOTA ( 68 Ga-DOTA-TOC) to diagnose cancerous lesions [53][54][55].…”
Section: Small Molecule Clinical Applications Of 68 Gamentioning
confidence: 99%
“…PET/CT studies with different agents have shown that 18 F-FDG PET/CT is useful in the diagnosis of EHE as well as in the detection of recurrence 7 . 68 Ga-DOTATATE PET/CT imaging showed intense activity uptake in EHE metastases 8 . 68 Ga-FAPI PET/CT has been shown to be superior to 18 F-FDG PET/CT in bone metastases of EHE 9 .…”
mentioning
confidence: 96%